The Effect of Scaffolding-Based Problem-Based Learning Approaches to Improve Mathematical Modelling Ability of Elementary School Students - Ariyanti Ariyanti; Neni Hermita (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2020)
This study aims to examine the improvement of mathematical modeling skills by using a problem-based learning approach based on scaffolding in elementary school students and to see the effect of the interaction between the learning approaches applied (PBL-based scaffolding and conventional) and the students' initial mathematical ability to improve mathematical modeling abilities. This research was conducted in 3 elementary schools located in the city of Bandung with the number of research subject classes consisting of 2 classes namely the experimental class and the control class. Experimental class getting learning with problem based learning approach based on scaffolding and control class getting conventional learning.The research design uses Quasi-Experimental design with pre-posttest design. The results showed that the increase in mathematical modeling skills in students who were given learning with PBL based on scaffolding was higher than students who were taught conventionally and there was an influence of interaction between the learning approaches applied (PBL based on scaffolding and conventional) and the students' initial mathematical ability towards increasing mathematical modeling ability.